Role of yqiC in the Pathogenicity of Salmonella and Innate Immune Responses of Human Intestinal Epithelium - Wang, Ke-Chuan; Huang, Chih-Hung; Ding, Shih-Min; Chen, Ching-Kuo; Fang, Hsu-Wei; Huang, Ming-Te; Fang, Shiuh-Bin (Frontiers in Microbiology, 2016)
The yqiC gene of Salmonella enterica serovar Typhimurium (S. Typhimurium) regulates bacterial growth at different temperatures and mice survival after infection. However, the role of yqiC in bacterial colonization and host immunity remains unknown. We infected human LS174T, Caco-2, HeLa, and THP-1 cells with S. Typhimurium wild-type SL1344, its yqiC mutant, and its complemented strain. Bacterial colonization and internalization in the four cell lines significantly reduced on yqiC depletion. Postinfection production of interleukin-8 and human β-defensin-3 in LS174T cells significantly reduced because of yqiC deleted in S. Typhimurium. The phenotype of yqiC mutant exhibited few and short flagella, fimbriae on the cell surface, enhanced biofilm formation, upregulated type-1 fimbriae expression, and reduced bacterial motility. Type-1 fimbriae, flagella, SPI-1, and SPI-2 gene expression was quantified using real-time PCR. The data show that deletion of yqiC upregulated fimA and fimZ expression and downregulated flhD, fliZ, invA, and sseB expression. Furthermore, thin-layer chromatography and high-performance liquid chromatography revealed the absence of menaquinone in the yqiC mutant, thus validating the importance of yqiC in the bacterial electron transport chain. Therefore, YqiC can negatively regulate FimZ for type-1 fimbriae expression and manipulate the functions of its downstream virulence factors including flagella, SPI-1, and SPI-2 effectors.